Feline herpesvirus type 1 infection alters the diversity of upper respiratory tract microbiota in cats - Li, Liyang; Feng, Wen; Bi, Lanxinyue; Deng, Ganzhen (Frontiers in Veterinary Science, 2025)
IntroductionFeline herpesvirus type 1 (FHV-1) is a primary pathogen causing feline upper respiratory tract diseases (FURTD), but its impact on the upper respiratory tract microbiota remains unclear. This study aimed to evaluate the impact of FHV-1 infection on the upper respiratory tract microbiota by comparing the microbial composition between FHV-1-positive group with FHV-1-negative group.MethodsThe microbial diversity in the upper respiratory tract of FHV-1-positive cats (n = 8) were analyzed using 16S rRNA high-throughput sequencing, and then this diversity was compared with that in healthy FHV-1-negative controls (n = 4).ResultsSequencing results showed that FHV-1 infection significantly increased microbial diversity (Shannon index: 5.55 ± 0.17 vs. 5.30 ± 0.11, p < 0.05; Simpson index: 0.95 ± 0.01 vs. 0.94 ± 0.00, p < 0.01) and altered community structure, as indicated by beta diversity analysis. At the phylum level, Actinobacteriota showed significantly higher relative abundance in the FHV-1-positive group than in the FHV-1-negative control group (p < 0.05). For the genus level, Porphyromonas and Bergeyella were significantly less abundant in FHV-1-positive group versus FHV-1-negative healthy control group (p < 0.05). Linear discriminant analysis effect size (LEfSe) identified Prevotellaceae as a biomarker for the FHV-1-positive group.DiscussionThis study provided the first evidence that FHV-1 infection significantly alters the diversity and composition of the upper respiratory tract microbiota in cats. These microbiota changes were likely to play an important role in the pathogenesis of FURTD and offer new targets for the development of microbiota-based therapeutic strategies.